A decisão brasileira de participar da MINUSTAH - Sá, Jessica Espíndola de (2015)
This dissertation aims to describe and to analyze the Brazilian decision to participate of MINUSTAH and the factors that have influenced it. It is the UN peacekeeping operation that most projects Brazil’s image in the International scenario due to the leading role assumed by the country, and also for being the main contributor of troops. The political decision of a state, concerning a foreign policy, is a complex process that involves several stakeholders and important factors to be evaluated and pondered in order to reach a final decision. Brazil’s participation in Haiti is assumed to be motivated by various factors, ranging from solidarity to a “brother country” and humanitarian assistance to pragmatic interests, such as the power projection. To define this process of decision-making, it will be analyzed some important factors, such as internal and external conjuncture, the domestic and international stakeholders involved, national and collective interests and the values and beliefs defended by decision makers.